Impact of weight changes on cardiometabolic markers among low socioeconomic overweight and obese women in a community lifestyle intervention - Ahmad Zamri, Liyana (2019)
Weight loss has been linked to improvements in multiple cardiometabolic risk factors, including lipid profiles, glucose and insulin sensitivity. However, weight loss intervention and its health benefits among low-income women, a group with a higher risk of obesity, have received little attention, particularly in the local setting. The current study utilised the secondary outcomes of a community-based lifestyle intervention namely My Body is Fit and Fabulous at Home (MYBFF@home) to investigate the impact of weight changes on cardiometabolic risk markers among low socioeconomic women in three different study phases (i.e., overall 12 months (baseline to 12 months), weight loss intervention phase (baseline to 6 months) and weight loss maintenance phase (6 to 12 months). This study also further explored the association between weight changes and improvements in those risk markers. MYBFF@home was a quasi-experimental study of overweight and obese women living in low-cost flats in Klang Valley. The intervention group underwent a 6-month lifestyle intervention that included individual diet counselling, moderate-intensity physical activities, and self-monitoring skills (using a pedometer, diet, and physical activity diaries), after which they were followed up at 12 months. The control group attended group seminars on women’s health during follow-up visits. In the current study, 243 participants (129 in the intervention group and 114 in the control group) were included in the analysis on an intention-to-treat basis. Anthropometric measurements (i.e., weight and waist circumference (WC) and blood samples were assessed at baseline, six months, and one year. Fasting plasma glucose (FPG), insulin, insulin resistance marker (HOMAIR), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides, adiponectin, high-sensitivity C-reactive protein (hs-CRP) and tumour necrosis factor-α (TNF-α) were measured in the blood samples. The participants were also stratified according to the change in body weight; 1) loss 5 to 20%, 2) loss > 2 to < 5%, 3) maintained ± 2% and 4) gained > 2%. Repeated measures ANCOVA revealed a significant intervention effect (Time x Group) on TC (F(2, 236) = 3.131, p = 0.046) and hs-CRP (F(2,288) = 4.129, p = 0.017) after 12 months controlling for age and baseline weight while no evidence found in other risk markers. The magnitude of weight change in the intervention group after 12 months was significantly correlated to improvement in WC (r(125) = 0.366, p < 0.001), FPG (r(125) = 0.228, p = 0.010), insulin (r(113) = 0.247, p = 0.008) and HOMA-IR (r(113) = 0.290, p = 0.002) after controlling for age and baseline weight. Participants in the intervention group who lost between 5 to 20% of their body weight showed highest reduction of WC (-5.67 cm [95% CI:-7.98,-3.36]), insulin (-4.27 μU/mL [95% CI:-7.35,-1.19]) and TC (- 0.59 mmol/L [95% CI:-0.99,-0.19]) as compared to other weight change categories. Those who lost > 2 to < 5% of body weight also showed reduction in WC (-4.24 cm [95% CI:-5.44,-3.04]) and insulin (-0.36 μU/mL [95% CI:-1.95, 1.24]) but not in TC. No evidence of association was found during the maintenance period in both study groups. For overall 12 months, a step-wise association in the changes of WC, FPG and insulin was observed in the intervention group but not in the control group except for WC. In conclusion, in the context of low socioeconomic communities, this study supports that weight loss-related lifestyle modifications over 6 months could improve selected cardiometabolic risk markers including TC, hs-CRP and markers of glycaemic control in overweight and obese women even with minimal weight loss (> 2% from initial body weight).